QM/MM simulations provide insight into the mechanism of bioluminescence triggering in ctenophore photoproteins. - Maryam Molakarimi; Ammar Mohseni; Majid Taghdir; Zaiddodine Pashandi; Michael A Gorman; Michael W Parker; Hossein Naderi-Manesh; Reza H Sajedi (PLoS ONE)
Photoproteins are responsible for light emission in a variety of marine ctenophores and coelenterates. The mechanism of light emission in both families occurs via the same reaction. However, the arrangement of amino acid residues surrounding the chromophore, and the catalytic mechanism of light emission is unknown for the ctenophore photoproteins. In this study, we used quantum mechanics/molecular mechanics (QM/MM) and site-directed mutagenesis studies to investigate the details of the catalytic mechanism in berovin, a member of the ctenophore family. In the absence of a crystal structure of the berovin-substrate complex, molecular docking was used to determine the binding mode of the protonated (2-hydroperoxy) and deprotonated (2-peroxy anion) forms of the substrate to berovin. A total of 13 mutants predicted to surround the binding site were targeted by site-directed mutagenesis which revealed their relative importance in substrate binding and catalysis. Molecular dynamics simulations and MM-PBSA (Molecular Mechanics Poisson-Boltzmann/surface area) calculations showed that electrostatic and polar solvation energy are +115.65 and -100.42 kcal/mol in the deprotonated form, respectively. QM/MM calculations and pKa analysis revealed the deprotonated form of substrate is unstable due to the generation of a dioxetane intermediate caused by nucleophilic attack of the substrate peroxy anion at its C3 position. This work also revealed that a hydrogen bonding network formed by a D158- R41-Y204 triad could be responsible for shuttling the proton from the 2- hydroperoxy group of the substrate to bulk solvent.